Harta Bersama Sebagai Objek Jaminan Perjanjian Kredit Bank - Aurora Mayawa Rissandjani; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
Social beings are part of domestic development, so is the need for investment. It's almost unbelievable an event if there is no credit agency. In the case of an engagement by a third party, it is stated that a credit agreement with collateral for joint assets carried out by a husband or wife must obtain the spouse's permission by means of participation during the ratification of the engagement. However, a conflict will arise if legal steps are carried out involving joint property without the permission of one of the partners, so it is not in sync with the applicable process. The purposes of this study are to analyze the validity of the use of joint assets as collateral without the consent of the husband or wife, the legal consequences of guaranteeing joint assets in a bank credit agreement without the consent of the husband or wife and legal settlement due to the guarantee of joint assets without the permission of the husband or wife. This type of research is normative legal research with a case and conceptual approach. Legal sources are primary and secondary legal sources, while data collection techniques are carried out by examining existing library materials which are then analyzed systematically. In this study, it was found that when carrying out a credit agreement by insuring joint assets, it must be recognized by both parties between the wife and husband and if it violates the subjective conditions, it can be canceled